The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m114.563494
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Snapshots during the Transition from a Cu(II) to Cu(I) Metal Center of a Lytic Polysaccharide Monooxygenase by X-ray Photoreduction

Abstract: Background: Lytic polysaccharide monooxygenases (LPMOs) exhibit a copper center that binds dioxygen for catalysis. Results: We present LPMO structures from Cu(II) to Cu(I) and analyze the transition with quantum mechanical calculations. Conclusion: Reduction changes the copper coordination state but requires only minor structural and electronic changes. Significance: These structures provide insight into LPMO catalytic activation for further mechanistic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
105
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 57 publications
13
105
1
Order By: Relevance
“…Kjaergaard et al (12) also confirmed the presence of this hydroxide/water using extended x-ray absorption fine structure spectroscopy. Although density corresponding to a hydroxide/water molecule in the fourth equatorial position has been observed in some LPMO structures, such density was not observed in the structure of NcLPMO9C, possibly because of photo-reduction of the copper by the x-ray beam (53). The EPR envelope though confirms a d (x2 Ϫ y2) ground state (g z Ͼ g x , g y ) typical for an elongated octahedron.…”
Section: Discussionmentioning
confidence: 73%
“…Kjaergaard et al (12) also confirmed the presence of this hydroxide/water using extended x-ray absorption fine structure spectroscopy. Although density corresponding to a hydroxide/water molecule in the fourth equatorial position has been observed in some LPMO structures, such density was not observed in the structure of NcLPMO9C, possibly because of photo-reduction of the copper by the x-ray beam (53). The EPR envelope though confirms a d (x2 Ϫ y2) ground state (g z Ͼ g x , g y ) typical for an elongated octahedron.…”
Section: Discussionmentioning
confidence: 73%
“…S5). These water molecules are absent in the reduced Cu + structure of EfaCBM33A (20), suggesting that in our structure of fusolin the Cu 2+ ion has not undergone complete photoreduction.…”
Section: +mentioning
confidence: 97%
“…In order to attain structural information on the active site coordination geometry of the copper in its resting Cu(II) state, a spiral data collection technique was applied to the rodshaped BaAA10 crystals inspired by the work presented in Gudmundsson et al 26 (See Tables S1 and Table 1 for crystallisation and data statistics summaries). As well as using this strategy, it was necessary to reduce the X-ray intensity significantly at only 5% transmission, resulting in fairly weak diffraction data.…”
Section: Structure Of the Cu(ii) Form Of Baaa10mentioning
confidence: 99%
“…Several studies have now shown that chitin-active AA10s appear to display distinct active site geometries to those observed for other LPMOs 26,30,31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation